Histo-Morphological Effect of The Small, Large Intestines and Stomach of Animal Models Treated With Aqueous Extract of Abelmoschus Esculentus - E. Obeten, Kebe; Etukudo, Ekom; O. Buhari, Muhamad; E. Tito, Andrew; Eno-obong Udo, Edet (Journal of Public Health International, 2022)
This study investigates the effect of Aqueous extract of abelmoschus esculentus on the microanatomy of the small, large intestine and stomach and the body weight of Wister rats. Twenty-one adults male wistar rats weighing between 100-120 grams were assigned into three groups consisting of seven rats each; Group A (control), Group B (low dose), and Group C (high dose). The rats in the control group were fed with fed with feed and water only while the rats in groups B and C were treated with 0.1mg/kg body weight and 3.0mg/kg body weight of abelmoschus esculentus respectively for 14 days. At the end of administration, the final weights of all rats were recorded before sacrifice using cervical dislocation and the small, large intestine and the stomach were harvested, processed and stained using H&E stain. The results were revealed as significant (p<0.05) increased in the mean body weight compared with the weight in the control groups and experimental groups. The treated animal groups revealed increased cellularity, focal metaplasia of the mucosal cells with villous disruption in the small intestine and dysplasia of the mucosal with loss of epithelial shape in large intestine. The stomach histology showed gastric pits with goblet cells smooth muscles layer and surface epithelium in the control group. Sections from the low dose treated group showed deep epithelical gastric pit areas with marked depletion of pits and goblet cells while the high dose treated group revealed dysplasia of gastric pits, goblet cells and smooth muscles appear mildly eroded.
Keywords: Large Intestine; Small Intestine; Stomach; Abelmoschus Esculentus; Aqueous Extract